PENGARUH POMI DAN NPK 16.16.16 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L.) - Khusnu Abdillah Siregar, MP; Lufita Nur Alfiah; Almuzafri (SUNGKAI, 2022)
Effect of POMI and NPK 16.16.16 on the Growth and Production of Soybean (Glycine max L.)”. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Pasir Pengaraian University, Rokan Hulu Regency. This research will be carried out for three months starting from October 2021 to December 2022 (Appendix 1). This study used a factorial completely randomized design (CRD) consisting of two factors. The first factor was the provision of POMI (Factor D) consisting of 4 levels and the second factor was NPK 16.16.16 (Factor P) which consisted of 4 levels so that 16 treatment combinations were obtained with 3 replications, so there were 48 experimental units. Each unit consisted of 12 plants per plot and 6 plants were used as observation samples so that the total plants were 576 plants. The purpose of this study was to determine the interaction effect and the main effect on the growth and production of shallots given POMI and NPK 16:16:16 fertilizer. The results of the study can be concluded as follows: The interaction of POMI 250 cc/plant (30 liters/ha) and NPK 16.16.16 2.5 grams/plant (300 kg/ha) gave a significant effect on the relative growth rate parameters at the age of 14-21 DAP , net assimilation rate at the age of 28-35, weight of root nodules, age of harvest, number of root nodules, effectiveness of root nodules and dry seed weight of cropping where the best treatment for dry weight of cropping seeds was a combination of POMI and NPK 16.16.16 (D2P3) 58, 33 grams per clump so that, it can increase production by 6.9 tons/ha.